Sacroiliac screws fixation navigated with three-dimensional printing personalized guide template for the treatment of posterior pelvic ring injury: A case report - Yang, Zhanyu; Sheng, Bin; Liu, Delong; Wang, Yiwei; Liu, Chao; Xiao, Rui (Frontiers in Surgery, 2023)
Objective Pelvic injuries refer to the disruption of the inherent structural and mechanical integrity of the pelvic ring. Sacroiliac screw fixation technique is often used for the treatment of posterior pelvic ring injury, which is prone to the iatrogenic injury. Various attempts were proposed to avoid iatrogenic injuries, while the executing processes are usually too cumbersome. The patient-personalized guide template based on 3D printing technology has been considered as a promising method, which can achieve lower deviation and higher accuracy in a simple and convenient way. We reported the first case of posterior pelvic ring injury using 3D printing personalized guide template with the verification of intraoperative CT. Methods The subject was a 74-year-old female with posterior pelvic ring injury. Two patient-specific guide templates were customized based on 3D printing technology, one for S1 and the other for S2. We used the guide templates for navigation to place the sacroiliac screws. The placement of screws was verified by intraoperative CT. Intraoperative and postoperative variables were collected. Results The technique helped us successfully insert the sacroiliac screws into the safe zone. The intraoperative blood loss was 23.03 mL, and the duration of operation was 62 minutes. The exposure dose during CT scanning was 7.025 mSv. The assessment of screws position was excellent. Furthermore, there was no sign of any functional impairment postoperatively. Conclusions Sacroiliac screws fixation with the assistance of 3D printing personalized guide template under the verification of intraoperative CT may be a promising method to treat posterior pelvic ring injuries.